Barriers to Same‐Day Discharge of Patients Undergoing Total and Completion Thyroidectomy. (3rd February 2014) - Rutledge, Jonathan; Siegel, Eric; Belcher, Ryan; Bodenner, Donald; Stack, Brendan C.
Abstract : Objective: Describe barriers to same‐day surgery for patients undergoing total and completion thyroidectomy. Study Design: Case series with chart review. Setting: Academic health sciences center. Subjects and Methods: The subjects were patients who underwent total thyroidectomy or completion thyroidectomy and remained in hospital overnight or longer. A review was performed on patients who were operated on by a single surgeon from July 2005 through June 2013. Results: Two hundred and sixty‐eight cases were planned for same‐day surgery. One hundred patients were not discharged on the same day (37%). Patients observed overnight or admitted to hospital had significantly lower postoperative calcium levels, 8.4 mg/dL ( P <. 0001), and lower intraoperative parathyroid hormone (PTH), mean 6.0 pg/mL ( P <. 0001). Those significantly more likely to require overnight observation were male patients ( P =. 0117), black patients ( P =. 0045), those with completion thyroidectomy ( P =. 0039), and those with a complication of surgery ( P =. 003). Conclusion: Intraoperative PTH less than 10 pg/mL was the most frequent factor (25.7%) precluding same‐day discharge, followed by admission for social/financial/transportation reasons (22.6%), large dead space from goiter (15.5%), multiple comorbidities (13.4%), multiple surgical reasons (5.2%), airway observation (5.2%), pain management (3.1%), and intractable nausea due to general anesthetic (2.1%). Hypocalcemia and postoperative bleeding still remain obstacles to outpatient thyroid surgery; however, the use of rapid PTH testing, modern hemostatic techniques, appropriate calcium prophylaxis, and experienced clinical decision making can effectively stratify which patients require overnight observation.